Global media perspectives on the crisis in Panama - Hensel, Howard M.; Michaud, Nelson (Ashgate Pub., 2011)
Operation Just Cause, the United States' incursion into Panama, was the culmination of a gradually escalating confrontation between the United States and the Noriega dominated government of Panama that extended from June, 1987 until early January, 1990. This book analyzes the crisis from the perspective of the US, Canadian, French, Arab, and more.